2016
DOI: 10.1007/s40565-016-0216-5
|View full text |Cite
|
Sign up to set email alerts
|

Location methods of oscillation sources in power systems: a survey

Abstract: The deployment of a synchrophasor-based widearea measurement system (WAMS) in a power grid largely improves the observability of power system dynamics and the operator's real-time situational awareness for potential stability issues. The WAMS in many power grids has successfully captured system oscillation events, e.g. poorly damped natural oscillations and forced oscillations, from time to time. To identify the root cause of an observed oscillation event for further mitigation actions, many methods have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 34 publications
0
52
0
Order By: Relevance
“…Besides poorly damped oscillation, it is well recognized that there is another common type of low‐frequency oscillation, known as forced oscillation. Extensive research has been reported on the subject …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides poorly damped oscillation, it is well recognized that there is another common type of low‐frequency oscillation, known as forced oscillation. Extensive research has been reported on the subject …”
Section: Introductionmentioning
confidence: 99%
“…More specifically, methods for locating forced oscillation sources are proposed recently in the literatures . Wang and Sun gives a comprehensive review of the location methods and elaborates on their advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon of power system oscillation can be caused by many factors such as insufficient system damping, forced oscillation [2], external periodic load perturbation [3], parametric resonance [4] and modal interaction [5], etc. Conventionally, this problem can be partially solved by fine-tuning the parameters of power system stabilizers (PSSs) of the involved generators.…”
Section: Introductionmentioning
confidence: 99%